2012
DOI: 10.1016/j.jtcvs.2011.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining successful computed tomography–guided localization of lung nodules

Abstract: The distance between the hook wire tip and pleural surface was the major significant factor for successful computed tomography-guided nodule localization for subsequent video-assisted thoracic surgery resection. Thus, the localization of a hook wire adjacent to a target nodule with sufficient depth from the pleural surface is crucial to the success of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
67
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 31 publications
1
67
1
2
Order By: Relevance
“…Previous study (30) showed that the malignancy rates were 63% for part-solid GGO, 18% for pure GGO, and only 7% for solid nodules, similar to ours. Because of the small number cases, our data just can't reflect the probability well despite the fact that the malignancy rate is up to 60%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous study (30) showed that the malignancy rates were 63% for part-solid GGO, 18% for pure GGO, and only 7% for solid nodules, similar to ours. Because of the small number cases, our data just can't reflect the probability well despite the fact that the malignancy rate is up to 60%.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have showed that pneumothorax and pulmonary hemorrhage, with an incidence of 32.1-68% and 10.3-36%, respectively, in preoperative hook wire placement (22,29,30). Ichinose and colleagues represented similar result, of 500 lesions underwent CT-guided localization, pneumothorax was observed in 49% of the patients immediately after location, only 4.6% require intervention (22), much higher than other study (apply double-thorn hook wire) reported (18.6% and 24.4%) (23).…”
Section: Discussionmentioning
confidence: 99%
“…A failure to localize nodules disturbs the success of the thoracoscopic resection and leads to conversion to thoracotomy (4, 5). There are two kinds of localizing procedures: marking with thoracoscopically directly visible materials and marking with radio-opaque materials.…”
Section: Introductionmentioning
confidence: 99%
“…Percutan, műtét előtti jelölési lehetőségek, hogy CTvezérléssel valamilyen eszközt -drótot vagy speciális anyagot, mint technéciumizotóppal ( 99m Tc) jelzett makroaggregált albumint -juttatnak a góc közelébe, megkönnyítve a műtét alatti felkeresést. Tekintettel arra, hogy invazív módon, a mellkasfalon keresztül történik a jelölés, szövődményként felléphet a leggyakrabban légmell és pulmonalis bevérzés, ritkán vérköpés vagy légem-bolia [15][16][17]. Szövődményekkel és a műtét szervezésével kapcsolatban további technikai probléma, hogy általában külön helyiségben történik a góc jelölése és az operáció, ami megnehezíti egyes szövődmények azonnali, akár a műtéttel egyidejű ellátását.…”
unclassified